Reading In memoriam - Peltason, Timothy, 1951- (Princeton, New Jersey : Princeton University, 1985)
By making his argument about In Memoriam a continuous argument for it, Timothy Peltason brings to light a wider appreciation of its greatness and of its central place in the history of modern poetry. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Introduction -- The first movements of grief -- The poet's exemplary career -- Moments of vision -- The conditions of belief.
Includes indexes.
Includes bibliographical references (pages 171-176).
Print version record.
JSTOR
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892.; Hallam, Arthur Henry, -- 1811-1833 -- In literature; Hallam, Arthur Henry, -- 1811-1833 -- In literature; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892.; Hallam, Arthur Henry, -- 1811-1833; In memoriam (Tennyson, Alfred Tennyson, Baron); Tennyson, Alfred; Elegiac poetry, English -- History and criticism; Poésie élégiaque anglaise -- Histoire et critique; POETRY -- European -- English, Irish, Scottish, Welsh; POETRY -- English, Irish, Scottish, Welsh; Elegiac poetry, English; Literature; Criticism, interpretation, etc